A novel glycyrrhizin acid-coated stent reduces neointimal formation in a rabbit iliac artery model - Teng, Shuai; Zhu, Zhaowei; Li, Yang; Hu, Xinqun; Fang, Zhenfei; Liu, Zhenjiang; Zhou, Shenghua (Frontiers in Pharmacology, 2023)
Most drug-eluting stents (DES) inhibit intimal hyperplasia but impair re-endothelization, this study aimed to evaluate the in vivo strut coverage and neointimal growth in a new glycyrrhizin acid (GA)- eluting stent. New Zealand White rabbits (n=20) with atherosclerotic plaques were implanted with iliac artery stents: bare metal stents (BMS), rapamycin, or GA-eluting stents. After in vivo IVUS assessment at 28 days, vessels were harvested for scanning electron microscopy and histology. After 4 weeks of follow-up, the stent area and area of the external elastic lamina (EEL) were comparable between groups. In comparison to BMSs, rapamycin or GA-eluting stents significantly reduced neointimal area, although GA-eluting stents had the lowest reduction. There were more uncovered struts for rapamycin-eluting stents and fewer for GA-eluting stents and BMS. The expression of eNOS in the GA-eluting stents was much higher than that in the BMS and rapamycin-eluting stents, even though endothelial coverage between struts was equivalent between BMS. GA-eluting stents markedly promoted re-endothelization and improved arterial healing compared with rapamycin-eluting stents in the rabbit atherosclerotic model.